Auditoria de gestión al departamento de crédito y su incidencia en la rentabilidad de la cooperativa de ahorro y crédito metrópolis Ltda. año 2021 - Bosquez Peña , Jarizza Jamileth (2022)
This research project was developed in the Cooperativa de Ahorro y Crédito Metrópolis Ltda., whose objective is to carry out a Management Audit to the credit department and its impact on the profitability of the Cooperativa de Ahorro y Crédito Metrópolis Ltda. To comply with the determination of the general objective, specific objectives were set, which consisted of verifying the level of compliance with the policies and procedures to grant a loan, evaluating the behavior of the credit portfolio and its effectiveness in collection and finally analyzing the financial indicators to know the financial-economic reality presented by the institution. The types of exploratory and descriptive research, the inductive, deductive and analytical methods were used, the research technique that was used was the interview followed by the research instruments, to obtain the necessary evidence that will serve as a basis for issuing conclusions and recommendations to improve the situation of the institution. Based on the investigation, the following was obtained as a result; the policies and procedures to grant a loan present a confidence level of 90% and a low risk level of 10%, the behavior of the loan portfolio presents a favorable situation because the collection management carried out by the cooperative is effective and efficient, finally the financial indicators that represent the reality of the institution that allow the management to make the right decisions were calculated